Design Student Worksheet on the Topic of Ratio to Support Students' Computational Thinking Skills - Dwi Jayanti, Regita; Cahyawaty, Dian; Mulyono, Budi; Hapizah, Hapizah (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
One of the important skills in the 21st century is Computational Thinking (CT) skills. In PISA 2021, computational thinking aspect is one of the aspects measured in the field of mathematical assessment. But in reality, the computational thinking skill of Indonesian students is yet relatively low. This is shown from the results of the PISA (Programme for International Student Assessment) test in 2022 that Indonesian students got a score 366 which is the score is still below the average PISA score of 472. The lowest score is especially in the field of mathematical literacy or numeracy because in the test conducted by PISA, the question framework made has an element of computational thinking. To overcome this, a learning tool is needed, namely Student Worksheet. Learning through student worksheet can support students' computational thinking skills. The type of research is development study with the aim of producing student worksheet of ratio topic that is valid and practical and can support CT skills. The problems contained in the student worksheet can be solved according to the stages of CT indicators so that students are more directed and can develop their CT skills. Grade VII students at a junior high school in Palembang are the subjects in this study. This research uses the ADDIE development model through five stages, namely: (1) Analyze; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. Data was collected and analyzed quantitatively using a table of validity and practicality criteria. The results of this study were obtained from the conclusion that the student worksheet was valid based on the comments and suggestions of the validator with an average percentage of validity of 84.86%. The average practicality of the student worksheet was 79.13%, which showed that the student worksheet were included in the practical criteria. In addition, the student worksheet developed contain problems that students solve in accordance with the stages of the computational thinking skills indicator. Abstrak Salah satu kemampuan yang penting pada abad-21 adalah kemampuan Computational Thinking (CT). Pada PISA 2021, aspek computational thinking merupakan salah satu aspek yang diukur dalam bidang asesmen matematika. Tetapi faktanya, kemampuan computational thinking peserta didik Indonesia masih pada kategori rendah. Hal ini dibuktikan dari hasil tes PISA (Programme for International Student Assessment) tahun 2022 bahwasanya peserta didik Indonesia mendapatkan skor 366 yang mana skor tersebut masih di bawah rata-rata skor PISA sebesar 472.  Skor terendah tersebut khususnya pada bidang literasi matematika atau numerasi sebab pada tes yang diadakan oleh PISA kerangka soal yang dibuat memiliki unsur computational thinking. Untuk mengatasi hal tersebut maka diperlukan perangkat pembelajaran yang digunakan yaitu Lembar Kerja Peserta Didik. Pembelajaran melalui lembar kerja peserta didik dapat menunjang kemampuan computational thinking peserta didik. Jenis penelitian ini adalah penelitian pengembangan dengan tujuan untuk menghasilkan lembar kerja peserta didik materi rasio yang valid dan praktis dan dapat mendukung kemampuan CT. Permasalahan yang terdapat pada lembar kerja dapat diselesaikan sesuai dengan tahapan indikator dari CT sehingga peserta didik lebih terarah dan bisa mengembangkan kemampuan CT. Peserta didik kelas VII di salah satu SMP di Palembang merupakan subjek pada penelitian ini. Penelitian ini menggunakan model pengembangan ADDIE melalui lima tahap, yaitu: (1) Analyze; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. Data dikumpulkan dan dianalisis dengan kuantitatif sesuai tabel kriteria kevalidan dan kepraktisan. Hasil penelitian yang mendapatkan kesimpulan bahwa lembar kerja peserta didik valid berdasarkan komentar dan saran dari validator dengan persentase rata – rata kevalidan sebesar 84,86%. Rata-rata kepraktisan lembar kerja peserta didik yaitu sebesar 79,13% yang menunjukkan bahwa lembar kerja termasuk pada kriteria praktis. Selain itu, lembar kerja peserta didik yang dikembangkan memuat permasalahan yang diselesaikan peserta didik sesuai dengan tahapan indikator kemampuan computational thinking.